Prevalence and correlates of physical activity among adolescents from Southern Brazil - Dumith,Samuel C (2010)
OBJECTIVE: To estimate the prevalence and identify correlates of physical activity among adolescents. METHODS: Cross-sectional study nested within a cohort of 4,325 subjects from the city of Pelotas, Southern Brazil, aged 14-15 years in 2008. Physical activity was analyzed using three different approaches: (1) prevalence of any leisure-time physical activity; (2) prevalence of any active commuting to school; and (3) prevalence of engaging in at least 300 minutes per week of both (1) and (2) combined. Independent variables included sociodemographic, behavioral, social, and biological characteristics, and number of different leisure-time physical activites practiced. Statistical analyses were carried out using Poisson regression. RESULTS: The proportion of adolescents involved in any type of leisure-time physical activity was 75.6%, while 73.4% displayed some form of active commuting to school. Prevalence of total physical activity score (> 300 min/week) was 48.2%, being greater among boys (62.6%) than among girls (34.5%). Furthermore, prevalence increased along with the number of physical activity modalities practiced (p<0.001). Factors associated with greater physical activity (leisure + commuting) at the recommended levels were: nonwhite skin color, having failed at school, and playing videogames. Lower socioeconomic status, more time spent on the computer, and parental physical activity were associated with the outcome only among girls. CONCLUSIONS: Less than half the adolescents reached recommended levels of physical activity, and this proportion tended to decrease among subjects with higher socioeconomic level. Associated factors were different for leisure-time and commuting. Engaging in a wide variety of physical activities should be encouraged already during childhood.